Prevalensi Obesitas dan Gambaran Kesehatan Kucing Peliharaan di RW. 13 Panyileukan, Kota Bandung - Hanifah, Nurul Dinan; Syamsunarno, Mas Rizky Anggun Adipura; Rosdianto, Aziiz Mardanarian (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Overweight and obesity are conditions that can occur not only in humans, but also in animals. Obesity in pet cats is the second highest health problem after oral disease in the United States and is said to be associated with a variety of metabolic or other disorders that can lead to a reduced quality of life. The prevalence of obesity varies from 6.7-42% in various countries. This study was conducted to determine the overview of pet cats’ health and the prevalence of obesity in pet cats in RW.13 Panyileukan, Bandung City. This descriptive study was conducted with a physical examination method approach with the use of 5-point BCS and observational using a questionnaire instrument. The results showed that there was one cat diagnosed as sick with flu-like symptoms such as fever, weak with liquid feces and the other sixteen cats were healthy and did not show any sickness. In addition, of the pet cats that had been examined there were two that indicated overweight, a cat was categorized as underweight while the remaining forteen cats were categorized as ideal body weight showing no indication of obesity overweight.the health overview of pet cats in RW.13 Panyileukan, Bandung City shows that 94% of cats are healthy and 6% of cats are sick, 82% of pets cats are categorized as healthy with ideal weight at BCS 3, 6% of cats are underweight in the category with BCS 2 and 12% of cats are categorized as overweight with BCS 4.